Swissregard.ch - a prospective registry on sudden death and aborted sudden cardiac death in Swiss athletes - Wilhelm, M.; Kellerhals, C.; Bolliger, S.; Schmied, C.; Wyler, D.; Nagel, R.; Bartsch, C.; Saner, H.; Michaud, K. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2011)
Sudden death of an athlete on the field is the most devastating medical event in sports. Incidences of sudden cardiac death (SCD) of 0.5 to 3.0 per 100 000 athletes per year have been reported. Data are derived from reviews of public media reports, available electronic resources and observational studies, and consequently underestimation is likely. The most common causes of SCD in young athletes are underlying congenital cardiac disease or blunt chest trauma (Commotio Cordis) in a structurally normal heart. Male athletes are affected in up to 90% of cases. Competitive team sports like soccer or basketball or endurance sports like marathon running are associated with the highest risk of dying suddenly. Geographical differences in the causes of SCD have been reported and the role of ethnicity still has to be clarified. Therefore there is a need for national registries prospectively recording cases of sudden death in athletes of different regions and ethnicities. The data will be valuable for international comparisons and in the debate of tailored national pre-participation screening programs. In cooperation with regional Institutes of Forensic Medicine we designed a web-based database for recording cases of sudden death in athletes in Switzerland prospectively since 2011.